Fibril‐Type Textile Electrodes Enabling Extremely High Areal Capacity through Pseudocapacitive Electroplating onto Chalcogenide Nanoparticle‐Encapsulated Fibrils (Adv. Sci. 33/2022). Issue 33 (24th November 2022) - Chang, Woojae; Nam, Donghyeon; Lee, Seokmin; Ko, Younji; Kwon, Cheong Hoon; Ko, Yongmin; Cho, Jinhan
Abstract : Energy Storage Devices In article number 2203800, Yongmin Ko, Jinhan Cho and co‐workers investigate fibril‐type textile electrodes which exhibit extremely high areal capacity from chalcogenide nanoparticle assembly‐driven pseudocapacitive electroplating process. Conductive and energy storage materials can be effectively introduced into 3D porous textiles by considering favorable interfacial interactions between each material. This approach plays a pivotal role in preparing high‐performance energy storage devices.